Pengaruh Substitusi Tepung Mocaf pada Tepung Terigu terhadap Karakteristik Mie Basah - Putri Afriliyanti; Hendrawan Hendrawan; Asep Hodijat (Ma'soem University, 2023)
The purpose of this study was to determine the appropriate percentage of mocaf flour substitution for the characteristics of the resulting wet noodles. The method used in this study was RAK with five treatments and five groups. The criteria for observations made on wet noodles included testing the water content, swelling power of the noodles, testing the elasticity of the noodles and organoleptik properties (taste, aroma and texture). The results showed that best percentage of mocaf flour substitution, namely treatment B (10%) has the best swelling power, the best elasticity and has the best texture compared to other mocaf flour substitution treatments.